Responsabilidad del Estado ecuatoriano en las sentencias emitidas por la Corte IDH en relación al control de convencionalidad - Inca Gualacio, Stephany Paulina (2024)
This research work responds to the problem of the limited use of conventionality control in Ecuador. The main objective is to analyze the responsibility of the Ecuadorian State in the judgments of the Inter-American Court of Human Rights for the violation of rights enshrined in the American Convention on Human Rights about the control of conventionality, which was achieved through documentary analysis of the resolutions of high national and international justice bodies. The methodology implemented included inductive, legal-analytical, historical-logical, and legal-doctrinal to study the relationship between the control of conventionality and the international responsibility of the Ecuadorian State. The approach was qualitative, while the type of research was characterized as pure, documentary-bibliographic, and legal-descriptive, which allowed the study of the jurisprudence of the Inter-American and Constitutional Court on the object of study. The results of the documentary analysis of the jurisprudence of the Inter-American Court of Human Rights indicated that the control of conventionality is an obligation of the States that have ratified this instrument, and the non-observance of this norm configures the international responsibility of the State. In the case of Ecuador, although the Constitution recognizes the direct applicability of international human rights instruments, there are still obstacles to the effective implementation of the control of conventionality, such as political will and the contrast with the control of constitutionality. The limited application of this mechanism in the country resulted in multiple declarations of state responsibility. Consequently, one of the State's obligations is to prevent these violations from occurring again